Immunotherapeutic strategies in antiphospholipid syndrome. Issue 3 (March 2017) - Hoi, A. Y.; Ross, L.; Day, J.; Buchanan, R. R. C.
Abstract : Antiphospholipid syndrome is an autoimmune condition, characterised by the persistent presence of antiphospholipid antibodies and either thrombosis or obstetric morbidity. The cornerstone of therapy is long‐term anticoagulation to reduce morbidity and mortality; however, better understanding of the immunological pathways may direct us to develop future therapeutic strategies. We provide an overview of the current understanding of the immunopathogenesis of this perplexing condition and its associated morbidities and current evidence for some of the immunotherapeutic strategies.